Analisis Model Penelusuran Backward Chaining dalam Mendeteksi Tingkat Kecanduan Game pada Anak - Anastasya Latubessy; Ahmad Jazuli (Jurnal Teknologi dan Sistem Komputer, 2017)
Game addiction rate can be detected by applying expert system. This study developed a model of game addiction analysis using backward chaining. This model uses six types of game addiction behavior, among others, salience, euphoria, conflict, tolerance, withdrawal, relapse and reinstatement. Someone is said to be addicted to the game if it meets at least three types of game addiction behavior. Testing the validity of the model is done by testing the closeness of the agreement between the model analysis and expert analysis, resulting in a value of 0.78 which means having a strong agreement.